Evaluating harm-reduction initiatives in a night-time economy and music festival context - Garius, Laura (International journal of comparative and applied criminal justice, 2020)
Pubs, clubs, and music festivals are places characterised by increased alcohol consumption. Drinkaware, a UK alcohol awareness charity, delivered two crime-prevention initiatives designed to reduce alcohol-related harm among young adults: the “Drinkaware Crew” initiative implemented at night-time-economy (NTE) venues, and more recently, the Drinkaware “Festival Crew”. This paper uses mixed methods to present (a) an outcome evaluation of the societal impact of the “Drinkaware Crew” initiative using routinely collected data; and (b) a process evaluation examining the transferability of the “Drinkaware Crew” initiative to a music festival-context. Findings indicate that the Drinkaware Crew occupy a unique gap in existing NTE and festival infrastructures, however, a number of improvements to the data available are recommended to ensure that such initiatives are thoroughly evidence-based.